A study into the balance of risks to mental and physical health from the 2020 lockdown and cessation of training for Brazilian Jiu Jitsu (BJJ) players in the UK versus the risks to physical health from Covid-19 - Martin, R. (2021)
The cessation of Martial Arts training during 2020 lockdown has meant hundreds of thousands of people are unable to practice their sport (1), with detrimental results for mental and physical health. (See survey results, appendix 1.) We have analysed the effect on mental and physical health with a self-administered questionnaire released via UKBJJA email lists and social media sites relating to Brazilian Jiu Jitsu. We have also analysed the prevalence of Covid-19 in the Martial Arts community using data gathered by the UKBJJA for elite athletes during lockdown, measuring athlete temperature and wellness for every training session. We found a negative effect on mental and physical health, with the majority of BJJ players gaining weight and losing fitness. Higher levels of alcohol and recreational drug use were also recorded. These negative effects could reduce life expectancy for the BJJ community.